ANALISIS PENGARUH KANDUNGAN GAS TETRAFLOROETANA TERHADAP KEKUATAN DIELEKTRIK GAS KARBONDIOKSIDA DALAM MEDAN TINGGI DC NON-HOMOGEN - Ivan Aditya Chrissanto; Moch. Dhofir; Tri Nurwati (Jurnal Mahasiswa TEUB, 2023)
This study discusses the effect of the gas concentration of tetrafluoroethane (R-134) on the dielectric of carbondioxide gas (CO2) in a non-homogeneous DC high field. The influence analyzed is the dielectric strength. This research was carried out using variations in the condition of changes in the concentration of R-134 gas, the total pressure of the mixed gas, and the distance between the electrodes. Variations in the concentration of R-134 gas in carbondioxide gas are 0%, 10%, 20%, and 30% which are calculated based on the total pressure of the mixed gas. The variations in the total pressure of the mixed gas are 2000 mBar, 2200 mBar, 2400 mBar, and 2600 mBar. The variation of the gap between the two electrodes is 1,5 cm and 3 cm. Furthermore, distribution simulations and calculations of electric field efficiency were carried out using FEMM 4.2 software, so that the dielectric strength values could be calculated. The results obtained in this study are the greater the concentration of gas R-134 given, the higher the value of the dielectric strength. At the same concentration of R-134 gas, an increase in the total pressure of the mixed gas and the value of the gap also causes an increase in the value of the dielectric strength.Keywords: dielectric strength, gas insulator, carbondioxide, tetrafluoroethane